EVALUASI PENGGUNAAN OBAT ANTIBIOTIK PADA PASIEN BALITA YANG TERDIAGNOSA DIARE DI KLINIK ISYKARIMA CIKARANG - Siti Latifah; Dadan Ridwanuloh; Himyatul Hidayah (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2022)
Due to the increasing number of people experiencing diarrhea every year, it has long been considered one of the most severe public health problems in the world. As a result, diarrhea is a significant cause of death in children under 5 years of age. The Ministry of Health of the Republic of Indonesia conducted an incident survey, which revealed that 1,637,708 diarrhea patients were treated in health care institutions, or 40.90 percent of the projected number of diarrhea patients. This study aims to determine whether antibiotics are effective in treating diarrhea in children under five at Isykarima Clinic Cikarang when used according to patient characteristics, indications, drug selection, and the right dose. This descriptive study used a cross sectional technique. This study used a descriptive observational research approach, in which prescriptions and test results from medical records (MR) were collected and recorded. By using retrospective data collection method. According to the research that has been done, it can be concluded that the male gender who suffers from diarrhea is 44 toddlers (55%). The rationale for the use of diarrhea drugs in patients under five according to the criteria for the right indication (100%), the right dose (100%), the right patient (100%), and the right drug (100%). The clinic has used antibiotics as indicated. According to usage, the most widely used antibiotic is cotrimoxazole.